2021
DOI: 10.1002/jcp.30271
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: MicroRNA‐4429 restrains colorectal cancer cell invasion and migration via regulating SMAD3‐induced epithelial–mesenchymal transition

Abstract: Colorectal cancer (CRC) is one of the commonest human cancers and the fourth primary cause of cancer‐related death. Previous studies have reported that miR‐4429 develops anticancer function in follicular thyroid carcinoma and non‐small cell lung cancer. However, whether miR‐4429 is implicated in the CRC progression remains to be clarified. The aim of our current study was to explore the potential role of miR‐4429 in CRC. According to the result of quantitative real‐time polymerase chain reaction analysis, miR‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…SMAD4 is a tumor suppressor gene that plays a central role in TGF-β signaling pathway transduction [25]. In CRC, SMAD3 reduces its expression through miR-4429 and ultimately inhibits the occurrence, development, and metastasis of cancer cells [26]. A meta-analysis showed that a high mutation rate of SMAD4 in CRC patients was associated with poor prognosis but not with clinical stage [27].…”
Section: Discussionmentioning
confidence: 99%
“…SMAD4 is a tumor suppressor gene that plays a central role in TGF-β signaling pathway transduction [25]. In CRC, SMAD3 reduces its expression through miR-4429 and ultimately inhibits the occurrence, development, and metastasis of cancer cells [26]. A meta-analysis showed that a high mutation rate of SMAD4 in CRC patients was associated with poor prognosis but not with clinical stage [27].…”
Section: Discussionmentioning
confidence: 99%
“…Smad3 plays important roles in the cell proliferation, invasion and metastasis of cancer cells, such as lung cancer ( 41 ), colorectal cancer ( 42 ), and chordoma ( 43 ). TGF-β could promote the progression of tumorigenesis in BC and facilitate cancer cell migration and invasion through the Smad3 signaling pathway ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 33 ) found that miR-4429 inhibits the growth of prostate cancer cells by downregulating DLX1 and inactivating the Wnt/β-catenin pathway. Li et al ( 34 ) demonstrated that miR-4429 blocks the proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) process of CRC cells by targeting FOXM1 to downregulate SMAD3. Cai et al ( 35 ) confirm that the silencing of lncRNA SNHG12 and overexpression of miR-4429 significantly inhibit the proliferation, migration and invasion of RL95-2 cells by downregulating MMP2 and MMP9 and targeting of the SNHG12/miR-4429 axis and can be used as a potential therapeutic target for endometrial cancer in the future.…”
Section: Discussionmentioning
confidence: 99%